6 Safety of ace inhibitors and spironolactone in paediatric heart disease. (2nd February 2018) - Abumehdi, MA; Hui, C; Smith, N; Liston, E; Hunter, L
Abstract : Purpose: ACE inhibitors (ACEi) and spironolactone are both used in the treatment of adult heart failure, due to their propensity to cause hyperkalemia and renal impairment in this ageing population, the concurrent administration is advised with caution by the Medicines and Healthcare products Regulatory Agency (MHRA). We aimed to investigate the safety of concomitant use in the paediatric population Methods: A single centre retrospective study of paediatric heart failure patients treated with a combination of Captopril and Spironolactone. Length of combination therapy; reason for therapy; urea and electrolytes pre and during treatment were analysed. The percentage change in each parameter was assessed compared to the recommended reference ranges for age. Results: 23 patients were commenced on a combination of Captopril and Spironolactone from January 2016 – June 2017 due to heart failure. In all cases urea and electrolytes were measured pre-treatment and at intervals during the therapy. The median duration of therapy was 56.7 days. Potassium levels demonstrated a median increase of 12.1%, none above the upper limits adjusted for age. Creatinine levels demonstrated a 1.7% decrease. Urea levels demonstrated a median increase of 5%, eight patients demonstrating a level above the upper reference range. Conclusion: Although a small study, we have demonstrated that Captopril and Spironolactone can be used safely and concurrently in the paediatric cohort in the absence of pre morbid renal dysfunction or dehydration. Intermittent monitoring of urea and electrolytes is essential during the treatment course.